THEORETICAL PRINCIPLES OF CONGESTION CONDITIONS RESEARCH - Pershakov, Valery; Krotov, Roman (Proceedings of National Aviation University (archive), 2015)
Recent years the number of vehicles on the roads increases continuously. This paper considers favorable factors of congestion. An example of a mathematical model of a situation of congestion on a regulated crossroad is provided. The dynamics of the queue congestion at crossroads, as well as its length is also showed.